Hormonal and Hydroxycinnamic Acids Profiles in Banana Leaves in Response to Various Periods of Water Stress. (26th May 2014) - Mahouachi, Jalel; López-Climent, María F.; Gómez-Cadenas, Aurelio
Abstract : The pattern of change in the endogenous levels of several plant hormones and hydroxycinnamic acids in addition to growth and photosynthetic performance was investigated in banana plants ( Musa acuminata cv. "Grand Nain") subjected to various cycles of drought. Water stress was imposed by withholding irrigation for six periods with subsequent rehydration. Data showed an increase in abscisic acid (ABA) and indole-3-acetic acid (IAA) levels, a transient increase in salicylic acid (SA) concentration, and no changes in jasmonic acid (JA) after each period of drought. Moreover, the levels of ferulic (FA) and cinnamic acids (CA) were increased, and plant growth and leaf gas exchange parameters were decreased by drought conditions. Overall, data suggest an involvement of hormones and hydroxycinnamic acids in plant avoidance of tissue dehydration. The increase in IAA concentration might alleviate the senescence of survival leaves and maintained cell elongation, and the accumulation of FA and CA could play a key role as a mechanism of photoprotection through leaf folding, contributing to the effect of ABA on inducing stomatal closure. Data also suggest that the role of SA similarly to JA might be limited to a transient and rapid increase at the onset of the first period of stress.